EVALUATION OF SAFETY OF DRUG THERAPY IN CLINICAL PRACTICE - M. N. Kostyleva; Yu. B. Belousov; A. N. Gratsianskaya; S. S. Postnikov (Фармакоэкономика, 2015)
the present review is devoted to an actual problem of safety of pharmacotherapy in clinical practice; the particular attention is paid to the state of this problem in pediatrics. Information about pharmacovigilance is proposed; criteria of definition, methods of collecting (their advantages and limitations), account and analysis of the adverse reactions of drugs in post-marketing period are described. The off label use of drugs in children and a role of clinical pharmacologist in the adverse reactions of drugs monitoring in a hospital is discussed.